1918
DOI: 10.1152/ajplegacy.1918.47.3.328
|View full text |Cite
|
Sign up to set email alerts
|

Two New Factors in Blood Coagulation—heparin and Pro-Antithrombin

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0
2

Year Published

1920
1920
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(85 citation statements)
references
References 0 publications
0
82
0
2
Order By: Relevance
“…Heparin (Howell,17,18),was used as the anticoagulant. Mechanical defibrination changes the white blood cells by destroying or removing many of the polynuclear cells as shown by Bull (20).…”
Section: Methodsmentioning
confidence: 99%
“…Heparin (Howell,17,18),was used as the anticoagulant. Mechanical defibrination changes the white blood cells by destroying or removing many of the polynuclear cells as shown by Bull (20).…”
Section: Methodsmentioning
confidence: 99%
“…Seu emprego permitiu o desenvolvimento e se tornou indispensável na cirurgia cardíaca com circulação extracorpórea, vascular, hemodiálise e procedimentos endovasculares. Nestes casos, além do benefício da anticoagulação imediata, possui a qualidade única, entre os anticoagulantes injetáveis, de ter um antídoto que permite sua reversão total, a protamina 4,5,6 . As heparinas denominadas não-fracionadas (HNF) são misturas heterogêneas com peso molecular médio de 15000 daltons e as heparinas de baixo peso molecular (HBPM) são preparadas por intermédio da despolimerização da HNF por meios químicos ou enzimáticos.…”
Section: Edi Torialunclassified
“…Maclean, a medical student working in the laboratory of W. H. Howell at the John Hopkins University at Baltimore, demonstrated that a phosphatide (cuorin) extracted from canine heart muscle prevented coagulation of the blood [2,6,15]. Subsequently, it was discovered that the active substance could also be extracted from dog liver in reasonable quantities and it was given the name 'heparin' [6,16]. The discovery of the anticoagulant property of heparin paved the way to the development of whole body perfusion in animals and, subsequently, extracorporeal oxygenators for use in human cardiac surgery [2,6].…”
Section: Progress Towards Whole Body Perfusion: Heparinmentioning
confidence: 99%